Biodegradation and bioelectricity generation of melanoidin in palm oil mill effluent (POME) by laccase-producing bacterial consortium integrated with microbial fuel cell. (August 2022) - Thipraksa, Junjira; Chaijak, Pimprapa; Michu, Panisa; Lertworapreecha, Monthon
Abstract: Melanoidin is the high molecular weight dark brown polymer in the palm oil mill effluent (POME) that is burdensome to degrade in the wastewater treatment process. In this study, the melanoidin degrading bacterial consortium was selected by culturing in synthetic POME and raw POME. Melanoidin removal and laccase activity were evaluated. The optimal conditions for melanoidin removal, such as initial pH, temperature, and culturing time have been studied. The consortium community has been analyzed using next-generation sequencing. The consortium was integrated with a microbial fuel cell (MFC) for electricity generation owing to the melanoidin degradation. The electrochemical properties, such as maximal current density (CD) and maximal power density (PD) generated from the MFC were similarly obtained. The results showed that consortium S5 mainly contains Citrobacter werkmanii, Enterococcus faecalis and Escherichia fergusonil showed the highest melanoidin removal of 86.02 ± 0.05%. The maximal CD and PD of 0.540 A/m 2 (21.60 A/m 3 ) and 0.080 W/m 2 (3.18 W/m 3 ) were achieved. The result indicated that the laccase-producing bacterial consortium was recommended for gaining the melanoidin removal and electricity generation from the POME in the MFC. Graphical abstract: Image 1 Highlights: The laccase-producing bacterial consortium selected from the soil sample showed the high potential for melanoidin removal. The consortium can degrade both the synthetic melanoidin and the POME melanoidin. The maximal PD of 3.18 W/m 3 was gained when 86% of melanoidin was removed.